Althusser, Machiavelli, and the PCF - Morfino, Vittorio (Filozofski vestnik, 2020)
In this essay I consider the fundamental features of Althusser’s reading of Machiavelli in its historical development, starting from the 1962 lecture course, passing through the 1972–76 course published with the title of Machiavel et nous as well as the writings of 1977–78, concluding with the group of writings written during the 1980s. I show that any teleological reading that sees in the final writings the truth finally revealed of the path of Althusser’s reading of Machiavelli (or its inversion, that is, the path itself as a corruption of an original truth) should be rejected, and instead present the thesis that Althusser, through the figure of Machiavelli, theoretically reworks his relationship with the Party.